Pengaruh Program K3 Terhadap Produktivitas Kerja pada Operator Alat Berat di PT BJTI Kota Surabaya - Friska Ayu; Denis Fidita Karya; Muslikha Nourma Rhomadhoni (Jurnal Bisnis dan Keuangan, 2019)
More than 2 million people/years died due to work accidents and occupational disease (ILO, 2010), while at Indonesia showed every 7 second work accident was occurs. BJTI Port is a port service provider company that carries out activities as a port terminal operator. Heavy equip- ment operator is one of the high-risk jobs, therefore this company must arrange work program that support the occupational health and safety management implementation at workplace through Safety Culture Implementation. Analyze Influence Occupational Health and Safety Program to Productiv- ity of Work to Heavy Equipment Worker at PT Berlian Jasa Terminal Indonesia Surabaya is the aim of this research. Total samples of 52 workers, taken by the total sampling method. Data related to respondent characteristics like productivity of worker and OHS Program obtained from direct observation to the field and interviews with all workers. The research results showed that as many as heavy equipment operators (55,7%) had high productivity. The statistical test using ordinal regression test indicate that there is an influence between the OHS Program with Productivity of Work to Heavy Equipment Operator at BJTI Port (0,000<0,05). Implementation of OHS Program at BJTI Port was good and need to be maintained, if possible, it can be improved by increasing the competency of OHS Supervisors and OHS management accordance with OHS regulations. In addi- tion its necessary to conduct surveillance of OHS devices, especially in areas that are rarely tra- versed by OHS supervisor.